Social work in the context of assisted dying in the Autonomous Community of Madrid - García Aguña, Sonia (Cuadernos de Trabajo Social, 2024)
In Spain, assisted dying (euthanasia and medically assisted suicide) was legalized in 2021 through Basic Law 3/2021 on the regulation of euthanasia. Social work initiatives are included in this legislation.. The aim of this article was to identify how the social dimension and social work are conceived in Basic Law 3/2021 on the regulation of euthanasia and, specifically, in the Guarantee and Evaluation Commission of the Community of Madrid. For this purpose, a qualitative exploratory study was carried out using in-depth semi-structured interviews with expert key informants. The sample was made up of seven specialist professionals with a direct (member) or indirect relationship with the Guarantee and Evaluation Commission. The main results indicate that social work professionals do not have the same recognition as other professionals in the Guarantee and Evaluation Commission. This hinders the biopsychosocial and holistic approach that the healthcare authorities are currently pursuing.